ANALYSIS OF TOTAL QUALITY MANAGEMENT IN DETERMINATION BUSINESS DONAT BU SULASTRI IN KEPANJENKIDUL DISTRICT - Novi Nurchasanah; Indria Guntarayana; Ama Fauziah (JOSAR (Journal of Students Academic Research), 2020)
This research was conducted with the aim to determine the effect of Retail Service, Marketing Mix, Product Quality, Word of Mouth on Consumer Satisfaction and Loyalty and Total Quality Management as an intervening variable. The respondents in this study were consumers who had bought at least two donut products at the IKM Donut Bu Sulastri, Kepanjenkidul Village, Kepanjenkidul District, Blitar City. The respondents in this study were 100 people. The method used in this research is the Mix Method and the data is processed using SmartPLS. The research results that refer to 11 hypotheses submitted by researchers get positive or significant results and are weak or rejected. The results of this study are expected to be able to connect the theoretical implications and managerial implications for the company with the findings of the innovations and the strategy implications explained in the closing chapter in the concluding sub-section.